Influence of Dietary Protein Source and Utilisation of Copra Meal in Finishing Broiler Chicken - Devi, Ashika; Diarra, Siaka Seriba (Indian Journal of Animal Nutrition, 2017)
The effect of dietary protein sources on the utilisation of copra meal was investigated in Cobb broilers. A control finisher diet based on fish meal (FM), meat and bone meal (MBM) and full-fat soybean (FFSB) and four other diets containing expeller copra meal (ECM) with combinations of these traditional protein sources (FM+ MBM, FFSB+FM, FFSB+FM+MBM and FFSB+MBM) were fed each to 4 replicates of 5 birds each in a completely randomized design. Body weight gain was highest (P